Sustainability and Built Environment: The role of Higher Education in Architecture and Building Engineering - Conte, Emilia (European Journal of Sustainable Development, 2016)
The sustainability paradigm implies a cultural shift in order to really change the world and society. Education, and specifically higher education, plays the crucial role of preparing students to be not only responsible citizens but also actors and promoters of processes and actions for a sustainable development. This is important in general and even more significant in architecture and engineering fields, as those students will be the designers of the built environment of tomorrow. This paper draws inspiration from the author’s practical experience for more than twenty years in teaching university courses in building technology and sustainable design for undergraduate and graduate students in civil and building engineering, tutoring their stages at professional studios, and supervising their theses. Moving from these premises, the author reports on and discusses some theoretical and practical outcomes concerning the: interpretation of built environment, design process, knowledge related to sustainability, use of a holistic approach in teaching sustainability, and collaboration among professionals. Finally, conclusions sketch potentials of new professionalisms for the sustainable future of built environment. Keywords: Sustainability Education, Built Environment, Building Engineering, Design Process